STRATEGI PEMBELAJARAN DENGAN MENGGUNAKAN E-LEARNING DI ERA DIGITALISASI - Arifin, Muhammad; Amiruddin, Amiruddin; Sari, Feby Nur Indah; Diana, Nelva (Hijri, 2024)
The current digital era has greatly influenced technological developments, especially in the learning strategy of using e-learning, making this a new medium for students in learning where e-learning is able to minimize differences in teaching methods and materials thereby providing more consistent learning quality standards. Where e-learning elerning is a very effective and efficient medium because it can be accessed anytime and anywhere. Therefore, this research was created with the aim of making readers familiar with e-learning as a learning strategy using literature review. Therefore, it is hoped that with this research, the education unit will be able to find out what the advantages and disadvantages are when using e-learning as a learning strategy.